First Report of Atretic Coronary Sinus Stenting in a 5‐kg Infant Resulting in Dramatic Improvement of Ventricular Function in Functional Single Ventricle. (3rd July 2013) - El‐Said, Howaida; Hegde, Sanjeet; Moore, John
Abstract The patient was a male infant with L‐transposition of great arteries (L‐TGA), Ebstein's anomaly of the tricuspid valve, subvalvar aortic stenosis, ventricular septal defect (VSD), hypoplastic right ventricle, arch hypoplasia, and congenital complete heart block. He underwent a Norwood procedure, aortic arch repair, permanent pacemaker implantation, and a 3.5‐mm aortopulmonary shunt at 4 days of age. At the time of his surgery, left ventricular function was in the normal range (ejection fraction [EF] = 67%). However by 3 months of age, he was noted to have developed moderate–severe biventricular dysfunction (left ventricular ejection fraction [LVEF] = 34%). Atresia of the coronary sinus with a small left superior venacava (LSVC) and a bridging vein was discovered during cardiac catheterization at this time. The coronary sinus mean pressure was 17 mm Hg, and the common atrial mean pressure was 6 mmHg. We opened the atretic coronary sinus ostium using radiofrequency ablation and stent placement. There was dramatic improvement in ventricular function observed over a 2‐month period. Follow‐up cardiac catheterization 5 months later revealed the stent in the coronary sinus to be widely patent with no intimal buildup, and the ventricular function was normal (LVEF =58%). The patient had a bidirectional Glenn procedure with an uncomplicated postoperative course and is currently awaiting Fontan completion.